Fish gelation in skin and bone tissue engineering - Syazwani Ramli; Norhidayu Muhamad Zain (Penerbit Universiti Kebangsaan Malaysia, 2019)
Gelatin is a biomaterial commonly used in tissue engineering application as it offers biocompatibility feature that can attract cell attachment. The most abundant sources of gelatin usually come from porcine skins, bovine hides and cattle bones. However, the mammalian gelatins are rejected by some consumers due to religious reason or health concerns. The fish gelatin can become a good option to substitute the mammalian gelatins. This review provides insights on the use of fish gelatin in tissue engineering applications. The review is focusing on the application fish gelatin in two main areas which are skin tissue engineering and bone tissue engineering that been studied by researchers in journals and thesis report. The potential of fish gelatin to substitute mammalian in this field will provide an alternative for Muslims to choose a halal medical treatment for them.